Comparative evaluation of the effectiveness of nebulized dexmedetomidine V/S intravenous dexmedetomidine in blunting hemodynamic response to intubation – A prospective and randomized study - Gandhi, Monika; Singh, Swati; Agrawal, Arpit; Arora KK (Asian Journal of Medical Sciences, 2023)
Background: Endotracheal intubation stimulates sympathetic system causing transient increase in heart rate and blood pressure which may be detrimental in patients with cardiovascular and cerebrovascular comorbidities. Intravenous dexmedetomidine given preoperatively prevents these unfavorable changes caused by endotracheal intubation. Aims and Objectives: The aims of this study were to compare effectiveness of nebulized dexmedetomidine and intravenous dexmedetomidine given preoperatively in blunting hemodynamic response (HR) to intubation. Materials and Methods: One hundred and twenty ASA I and II patients (either gender between 18 and 60 years) undergoing elective surgeries under general anesthesia were randomized into two equal groups in this prospective and comparative study. Thirty minutes before induction, Group IV received dexmedetomidine 0.50 μg/kg (diluted with normal saline [NS] to 50 mL) as slow IV infusion and nebulization with 5 mL NS, while Group N received nebulization with dexmedetomidine 1 μg/kg mixed with NS up to 5 mL along with 50 mL NS given as slow IV infusion. HR and mean arterial pressure (MAP) were noted at different intervals until extubation. Sedation score using Ramsay Sedation Scale (post-administration of drug) and adverse effects were noted. Comparison of HR and MAP was done using unpaired “t” test (P=0.05). Results: IV dexmedetomidine and nebulized dexmedetomidine given pre-induction were comparable in reducing stress response to intubation. The sedation score in both groups was comparable post-administration of drug. The incidence of hypotension was significantly more in IV group. Conclusion: Nebulized dexmedetomidine was equally efficacious in blunting HR to intubation as IV dexmedetomidine with fewer side effects making its administration safer for maintaining hemodynamic stability.